EXAMINING THE PSYCHOLOGICAL EFFECTS OF EMPLOYEE ENGAGEMENT ON ORGANIZATIONAL PERFORMANCE - Adam Idris; Khalid Mahmud; Pema Lhamo (Yayasan Adra Karima Hubbi, 2026)
Employee engagement has become a critical factor in enhancing organizational performance. Engaged employees are believed to be more motivated, productive, and committed, which in turn leads to better organizational outcomes. Understanding the psychological effects of employee engagement is vital for organizations seeking to optimize their human capital and improve overall performance. This study aims to examine the psychological effects of employee engagement on organizational performance. The research explores how factors such as motivation, job satisfaction, and emotional commitment contribute to the relationship between employee engagement and organizational performance. A quantitative research design was employed, utilizing surveys to collect data from 350 employees across various industries. The survey measured employee engagement, psychological well-being, job satisfaction, and organizational performance using established scales. Statistical analyses were conducted to identify the correlations and causal relationships between these variables. The findings indicated a strong positive relationship between employee engagement and organizational performance. High levels of employee engagement were linked to increased job satisfaction, lower stress, and higher productivity. Additionally, engagement was found to mediate the relationship between job satisfaction and performance outcomes.